2018
DOI: 10.1080/10410236.2018.1431016
|View full text |Cite
|
Sign up to set email alerts
|

Sense-making, Socialization, and Stigma: Exploring Narratives Told in Families About Mental Illness

Abstract: Guided by Communicated Narrative Sense-making Theory (CNSM), the current study investigated mental illness (MI) narratives told within families and the lessons younger members learned from these stories. Individual, semi-structured interviews with young adults (N = 24) revealed that family members, mainly parents, share stories about the MIs of individual family members and narratives reflected themes of struggle and caution. Participants reported learning important lessons from these MI narratives (i.e., MI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…However, the current body of communication literature has yet to deeply explore mental conditions such as DDD. Scholars have explored related topics such as stigma and mental illness (Flood-Grady & Koenig Kellas, 2019), memorable messages about mental health (Greenwell, 2019), eating disorders (Vidovic et al, 2005), anxiety (McLaughlin & Hatzenbuehler, 2009), among others. As a field, we still have a long way to go in terms of understanding mental disorders and illness through the lens of communication.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current body of communication literature has yet to deeply explore mental conditions such as DDD. Scholars have explored related topics such as stigma and mental illness (Flood-Grady & Koenig Kellas, 2019), memorable messages about mental health (Greenwell, 2019), eating disorders (Vidovic et al, 2005), anxiety (McLaughlin & Hatzenbuehler, 2009), among others. As a field, we still have a long way to go in terms of understanding mental disorders and illness through the lens of communication.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in an online survey conducted in China, Li et al [50] found no relationship between contact levels and the mental illness stigma toward people with mental disorders. These mixed reviews support early learning through case studies to reduce stigma toward mental illness [51]. The Chinese Lay Theory also suggests collecting qualitative data from contemporary families regarding their views towards individuals with mental illness [16].…”
Section: Discussionmentioning
confidence: 99%
“…Narratives help individuals to create significance, in a way "that provides means for individual, social and organizational sensemaking" (Rantakari & Vaara, 2017, p. 271). At the patient level, communicating an illness story makes it easier for these individuals to understand their condition (e.g., in terms of identity) (Flood-Grady & Koenig-Kellas, 2019). The act of sharing narratives allows patients to "make sense of their collective circumstances and of the events that affect them" (Jordan et al, 2009, p. e15), which in turn creates the basis to address these conditions.…”
Section: Narratives As a Sensemaking Processmentioning
confidence: 99%